Advanced Tracers in PET Imaging of Cardiovascular Disease. (15th October 2014) - Li, Yesen; Zhang, Wei; Wu, Hua; Liu, Gang
Abstract : Cardiovascular disease is the leading cause of death worldwide. Molecular imaging with targeted tracers by positron emission tomography (PET) allows for the noninvasive detection and characterization of biological changes at the molecular level, leading to earlier disease detection, objective monitoring of therapies, and better prognostication of cardiovascular diseases progression. Here we review, the current role of PET in cardiovascular disease, with emphasize on tracers developed for PET imaging of cardiovascular diseases.